Communication Model of Mosque Youth Lifestyle in Religious Life in Semarang City - Oktav N, Saka Mahardika; Juhadi, Juhadi; Atmaja, Hamdan Tri; Brata, Nugroho Trisnu (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2023)
Communication Model Lifestyle of Islamic adolescents towards religious differences in addressing understanding. Differences between communities on understanding and behavior is a study to carry out a model of communication between Muslim adolescent communities in the city of Semarang. This study examines the communication model of the differences between the four young mosque activist communities (NU, Muhammadiyah, Tabligh, and LDII) in Semarang. The research method uses a qualitative approach. The research subjects of young mosque activists as the primary informants were based on a purposive sampling technique. The study results are a Communication Model between four religious communities that conflict over differences in understanding. The results of research on the lives of four Muslim communities on lifestyle differences lead to disputes between Muslim communities. Differences in Muslim lifestyles raise potential conflicts between the four Muslim communities of NU, Muhammadiyah, Tabligh, and LDII. The different problems can be integrated with the existence of a social communication model between the four Muslim communities in Semarang.